2007
DOI: 10.1161/01.str.0000259711.13490.23
|View full text |Cite
|
Sign up to set email alerts
|

Recanalization and Outcome After Intra-Arterial Thrombolysis in Middle Cerebral Artery and Internal Carotid Artery Occlusion

Abstract: Background and Purpose-Recent studies have reported sex differences in recanalization and outcome after intravenous thrombolysis (IVT) in acute ischemic stroke. Methods-We analyzed sex differences in outcome in consecutive patients with middle cerebral artery (MCA) M1 or M2 and internal carotid artery (ICA) occlusion treated with intra-arterial thrombolysis (IAT). Recanalization immediately after thrombolysis and outcome after 3 months were assessed. Results-Two hundred five patients (111 men) with MCA and 43 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 22 publications
1
42
1
Order By: Relevance
“…Our study is based on the Bernese stroke registry, a prospective database on patients with AIS [18][19][20]. Baseline and 3-month outcome data on consecutive AIS patients admitted to the Neurological Department of the University Hospital of Bern are collected.…”
Section: Methodsmentioning
confidence: 99%
“…Our study is based on the Bernese stroke registry, a prospective database on patients with AIS [18][19][20]. Baseline and 3-month outcome data on consecutive AIS patients admitted to the Neurological Department of the University Hospital of Bern are collected.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the presence of complete internal carotid artery (ICA) occlusion from the bulb to the terminus with MCA occlusion and no pial collateral flow from the anterior cerebral artery is a predictor of poor response to IV thrombolysis, even in patients treated in <3 h [12,24]. Even IAT has a relatively low probability of complete recanalization (compared to MCA branch occlusion, for example) in such patients, and when taken into consideration with other mitigating factors, such as advanced age, hypertension, and prolonged duration of ischemia, ICA terminus occlusion portends a poor prognosis regardless of recanalization method [25][26][27]. By comparison, patients with cervical ICA occlusion, with or without tandem MCA occlusion have a better prognosis than those with ICA terminus occlusion [28,29].…”
Section: Indicationsmentioning
confidence: 99%
“…Further studies reported that milder baseline stroke deficits, elevated systolic blood pressures, normal glucose values, smoking history, absence of atrial fibrillation, distal vessel occlusion, and thrombus length positively predicts post-thrombolytic recanalisation. Considering these risk factors in individual cases, perhaps patients with smaller chance for reperfusion/recanalisation could benefit from more aggressive interventions, such as intra-arterial fibrinolysis [12][13][14][15][16][17][18]. …”
mentioning
confidence: 99%